The long-term impact of severe head injury on the family - Richman, Alexandra Elizabeth (Department of Psychology, 2016)
The purpose of this study was to examine the impact of brain injury upon the family of the brain-injured patient. Although some research into the psychosocial sequelae following head injury and the direct and indirect effects of severe head-injury upon the family have been conducted, these studies have largely been of a quantitative nature. For this reason, and with a view to expanding upon the existing findings, the present study was qualitative in nature in order to gain an in-depth understanding of relatives' experience of living with and caring for a severely head-injured family member. In addition, ways in which family members coped with the impact of the brain injury were elicited. Participants were caregivers to 11 severely head-injured patients who were representative of a range of socio-economic groupings and racial classifications. Severity of head injury was controlled for and participants were interviewed two or more years after the head injury had occurred. Demographic and injury related data were elicited by means of a questionnaire. Thereafter, data was collected by means of in-depth semi-structured interviews. A number of indices were developed based on a qualitative and descriptive analysis of the data. The study found that the mam source of distress experienced by caregivers related to emotional rather than physical symptomatology. All types of family relationships were profoundly affected by the patient's brain injury, although the caregiver's relationship with the patient appeared most vulnerable. Formal sources of support were considered inadequate and most caregivers relied heavily on emotional support, particularly from an intimate source. Coping responses were dependent upon coping resources available. Families of brain-injured patients who were racially and socio-economically disadvantaged were subjected to additional stress related to the unavailability of services and the randomness with which services that were available were dispensed. Rehabilitation services appeared to be failing to meet the needs of "brain-injured families" (Brooks, 1984) as they concentrated on the patient's physical handicap rather than emotional sequelae of the head injury.